KETERSEDIAAN SARANA DAN PRASARANA PARIWISATA DI PANTAI GLAGAH WANGI BERDASARKAN PREFERENSI PENGUNJUNG - Zulfa, Elfia; Sudrajat, Agus Sarwo Edy (Program Studi Perencanaan Wilayah dan Kota, Fakultas Teknik, Universitas Semarang, 2023)
Tourism facilities and infrastructure can make one of the supports in tourist attraction, because if the availability of facilities and infrastructure is not well developed it will result in reduced interest in visiting tourists. So that it can affect the decline in the quality of the tour.The purpose of this study was to determine the availability of tourism facilities and infrastructure based on the preferences of visitors at Glagah Wangi Beach as seen from the conditions and functioning of infrastructure facilities in the tourist area. The conditions and functioning in question include basic facilities, complementary facilities, supporting facilities and infrastructure. The method used in this study is cross-tabulation analysis to find out and measure visitor preference scales in determining the conditions and functioning of objects seen, especially facilities and infrastructure.The results obtained in this study were that the availability of facilities and infrastructure concerning the condition and functioning of basic facilities was 75% very good (Tourism Transport, Stalls, Homestays), complementary facilities 45% very good (float tire rental, ATV), supporting facilities 60% good (souvenirs, places of worship) and 42% infrastructure is not good (transportation, parking, accessibility, energy sources, toilets, telecommunications, clean water).